10 nm three-dimensional localization using Bessel beam microscopy. (17th January 2020) - Chakraborty, Chumki; Islam, Md Anisul; Snoeyink, Craig
Abstract: The last decade has seen significant advances in 3D localization precision driven by demanding applications in biological super-resolution microscopy. These applications have been constrained by precision in the z direction, which had previously been limited to above 10 nm for general applications. Here we present sub-10 nm localization precision using Bessel beam microscopy (BBM) at application-relevant photon counts. BBM uses an axicon, a conical optical element, to transform the point spread function of a microscope to a Bessel pattern, the spatial frequency of which is a simple function of emitter depth. We describe the BBM optical system, outline a method for image analysis, and demonstrate localization of fluorescent silver core silica nanoparticles with better than 10 nm precision in all directions.